Learners’ Fillers in English - Arrasul, Abdul Rabbi; Mangendre, Yuliana; Akbar T.A, Famelanisa; Hardianti, Sitti (Applied Research on English Education (AREE), 2024)
This study aims to find out the type of fillers and factor influenced fillers in English Education Study Program. This research is a qualitative research with in-depth interview design. This data collection involved 7 learners from the 4th semester and 6th semester of English Education Study Program at Muhammadiyah University of Luwuk. This research applied the theory from Rose (1998), Oomen and Postman (2021) in finding the data. The result of this research indicates the learners of English Education Study Program in 4th semester mostly use unlexicalized fillers and the 6th semester mostly use lexicalized fillers. There some factor influenced learners in using fillers are nervousness, divided Attention, infrequent. The dominant factor is nervousness. In this research, the input is suggested for learners, to the department of English Education Study Program and to further researchers to find out more about fillers and factor influenced fillers happened.